Tamanho da amostra foliar para avaliação do estado nutricional de goiabeiras com e sem irrigação - Rozane, Danilo E. [UNESP]; Natale, William [UNESP]; Prado, Renato de M. [UNESP]; Barbosa, José C. [UNESP] (FapUNIFESP (SciELO), 2009)
The ideal size precision of the foliar sample determines manual work optimization, and also diminishes inherent errors in diagnosis reports of nutritional state. This work aimed to determine the size of the foliar samples and the sample error variation in guava plantations submitted to two hydric cultivations for the nutritional state diagnosis of this fruit. The work included two studies, both under an entirely randomized experimental design. Study 1 was carried out in an orchard under unirrigated cultivation with four treatments and six repetitions that consisted of leaf collection in 5, 10, 20 and 40 plants. Study 2 was carried out in an orchard under irrigated cultivation with five treatments and 10 repetitions that consisted of leaf collection in 10, 20, 30, 40 and 50 guava plants. It was concluded that in unirrigated orchards it is necessary to sample leaves in 40 plants in order to keep the macronutrients sample error between 5 to 10%. For the micronutrients, on the other hand, at least 40 plants were necessary and, if Fe and Zn were considered, the sample must be even larger. In irrigated orchards, leaves deriving from 10 plants were enough to keep the sample error between 5 to 10%. However, considering the micronutrients, it was necessary to sample 20 guava plants.
Ideal size of leaf sample for nutritional state evaluation of guava under irrigated and unirrigated cultivation
Keywords: Experiment; Foliar diagnosis; Plant nutrition; Psidium guajava; Sample; Psidium